STRATEGI DIGITAL MARKETING DI MASA PANDEMI COVID- 19: STUDI UMKM DI KOTA METRO - Andini, Gustarina; Bahrudin, Moh.; Abdul Ghofur, Ruslan (Distribusi - Journal of Management and Business, 2022)
Several Culinary MSME actors in Metro City during the Covid-19 period, experienced a decline in sales. One of them is Banana Chips Tunas. This causes business actors to experience significant losses. Therefore, it is necessary to have the right strategy in overcoming the problems that occur, for example by implementing a strategy for using digital marketing. This study explains the effectiveness of using digital marketing in increasing sales of culinary business actors, especially Tunas Metro Banana Chips during the Covid-19 pandemic. Researchers used qualitative research methods with a field research approach. Prior to the COVID-19 pandemic, sales of Tunas Banana Chips had increased but not significantly. After the covid-19 pandemic by changing marketing that was previously offline to digital marketing, sales have increased significantly due to the wider marketing reach. This shows that MSMEs that utilize digital marketing are able to survive in the midst of the Covid-19 pandemic.